Financial performance and corporate governance: Evidence from national development banks in Africa - Samantha Attridge; Yunnan Chen; Michael Mbate (Overseas Development Institute (ODI), 2021)
National development banks (NDBs) have huge potential to support their country's development strategies and the transition to low-carbon, climate-resilient economies. However, a perception of problematic governance and weak performance means that these banks may be overlooked, both in terms of their potential role in supporting national development, and as partners for international development finance institutions, international climate funds, donors and private actors. This perception is especially strong for African NDBs. Many operate in contexts of institutional weakness and problematic governance, presenting challenges both to the autonomy of NDBs from political interests, and the capacity of these institutions to fulfil their mandates. This study explores whether these negative perceptions of governance and financial performance are valid, and examines the extent to which the governance of NDBs in Africa affects their financial performance. Combining quantitative and descriptive analysis based on a novel time-series dataset of 33 banks in 21 countries, we explore the governance and financial trends that characterise these banks over the period 2014 to 2019, and use an econometric analysis to measure the specific impact of political influence on governance, and the financial performance of banks.
Keywords: 330; Economic growth; Africa; Governance; Development finance